Primary angioplasty in acute myocardial infarction with right bundle branch block: should new onset right bundle branch block be added to future guidelines as an indication for reperfusion therapy? - Widimsky, Petr; Rohác, Filip; Stásek, Josef; Kala, Petr; Rokyta, Richard; Kuzmanov, Boyko; Jakl, Martin; Poloczek, Martin; Kanovsky, Jan; Bernat, Ivo; Hlinomaz, Ota; Belohlávek, Jan; et al. (European heart journal, 2012)
AIMS: The current guidelines recommend reperfusion therapy in acute myocardial infarction (AMI) with ST-segment elevation or left bundle branch block (LBBB). Surprisingly, the right bundle branch block (RBBB) is not listed as an indication for reperfusion therapy. This study analysed patients with AMI presenting with RBBB [with or without left anterior hemiblock (LAH) or left posterior hemiblock (LPH)] and compared them with those presenting with LBBB or with other electrocardiographic (ECG) patterns. The aim was to describe angiographic patterns and primary angioplasty use in AMI patients with RBBB. METHODS AND RESULTS: A cohort of 6742 patients with AMI admitted to eight participating hospitals was analysed. Baseline clinical characteristics, ECG patterns, coronary angiographic, and echocardiographic data were correlated with the reperfusion therapies used and with in-hospital outcomes. Right bundle branch block was present in 6.3% of AMI patients: 2.8% had RBBB alone, 3.2% had RBBB + LAH, and 0.3% had RBBB + LPH. TIMI flow 0 in the infarct-related artery was present in 51.7% of RBBB patients vs. 39.4% of LBBB patients (P = 0.023). Primary percutaneous coronary intervention (PCI) was performed in 80.1% of RBBB patients vs. 68.3% of LBBB patients (P< 0.001). In-hospital mortality of RBBB patients was similar to LBBB (14.3 vs. 13.1%, P = 0.661). Patients with new or presumably new blocks had the highest (LBBB 15.8% and RBBB 15.4%) incidence of cardiogenic shock from all ECG subgroups. Percutaneous coronary intervention was done more frequently (84.8%) in patients with new or presumably new RBBB when compared with other patients with blocks (old RBBB 66.0%, old LBBB 62.3%, new or presumably new LBBB 73.0%). In-hospital mortality was highest (18.8%) among patients presenting with new or presumably new RBBB, followed by new or presumably new LBBB (13.2%), old LBBB (10.1%), and old RBBB (6.4%). Among 35 patients with acute left main coronary artery occlusion, 26% presented with RBBB (mostly with LAH) on the admission ECG. CONCLUSION: Acute myocardial infarction with RBBB is frequently caused by the complete occlusion of the infarct-related artery and is more frequently treated with primary PCI when compared with AMI + LBBB. In-hospital mortality of patients with AMI and RBBB is highest from all ECG presentations of AMI. Restoration of coronary flow by primary PCI may lead to resolution of the conduction delay on the discharge ECG. Right bundle branch block should strongly be considered for listing in future guidelines as a standard indication for reperfusion therapy, in the same way as LBBB.
Keywords: Coronary Occlusion; Humans; Myocardial Reperfusion; lidé středního věku; Electrocardiography; koronární okluze; balónková koronární angioplastika; Female; Aged; Longevity; výsledek terapie; senioři; lidé; infarkt myokardu; mortalita v nemocnicích; reperfuze myokardu; Angioplasty, Balloon, Coronary; Practice Guidelines as Topic; ženské pohlaví; Male; Middle Aged; Retrospective Studies; Myocardial Infarction; Treatment Outcome; dlouhověkost; blokáda Tawarova raménka; směrnice pro lékařskou praxi jako téma; retrospektivní studie; Bundle-Branch Block; Hospital Mortality; mužské pohlaví; elektrokardiografie